2008
DOI: 10.1590/s0074-02762008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviruses C in non-hospitalized Mexican children older than five years of age with acute respiratory infection

Abstract: Adenoviruses (AdV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
3
12
4
Order By: Relevance
“…These methods will be of direct use during outbreaks of a specific type when decision making is depended on these results. This method has been used by others for the detection the hexon gene region of Adenovirus genome [7,14,15]. Similar findings have been reported by Helen Sarantis et al, who tested hexon gene (HVR-7) that was able to detect all serotypes of human adenoviruses known at that time with high sensitivity [17].…”
Section: Resultssupporting
confidence: 64%
“…These methods will be of direct use during outbreaks of a specific type when decision making is depended on these results. This method has been used by others for the detection the hexon gene region of Adenovirus genome [7,14,15]. Similar findings have been reported by Helen Sarantis et al, who tested hexon gene (HVR-7) that was able to detect all serotypes of human adenoviruses known at that time with high sensitivity [17].…”
Section: Resultssupporting
confidence: 64%
“…In all four regions (northern coast, central coast, southern highlands, and jungle) subgroup C predominated, subgroup B was the second most common, and subgroup E was the least common (except for the central coast where B and E were identified in the same number). Likewise, the bordering country of Brazil [41], [56], as well as the non-bordering Latin American countries of Mexico [57] and Cuba [45], also observed a predominance of subgroup C. On the other hand, two other countries bordering Peru, Colombia [38], [58] and Argentina [43], noted a predominance of subgroup B.…”
Section: Discussionmentioning
confidence: 99%
“…They are important human pathogens, particularly in the immunocompromised (20,21), and are reported primarily as respiratory agents; HAdV-C infections may be mild or asymptomatic (7) or cause serious acute respiratory disease (5,7,(15)(16)(17)32).…”
mentioning
confidence: 99%
“…As an example, species C members have constituted up to 28.5% of the typed isolates in a epidemiologic survey of HAdV acute respiratory infections of children in South America in a 4-year period (17), indicating a significant presence in that population. Another report observed that 23% of the pathogens causing acute respiratory disease in 100 Mexican children were HAdVs, with all of the isolates identified as species C exclusively (32), including HAdV-C6. This was also observed in a recent survey of Malaysian HAdV respiratory tract infections, which noted that species C were the most commonly isolated HAdV among pediatric patients in a 7-year period (1).…”
mentioning
confidence: 99%